Multimodal Therapy of Upper Gastrointestinal Malignancies - Ronellenfitsch, Ulrich (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Recent decades have seen remarkable advances in the treatment of upper gastrointestinal malignancies, i.e., adenocarcinoma and squamous cell carcinoma as well as gastrointestinal stromal and other rare tumors of the esophagus and stomach. While, historically, surgical resection has been the sole treatment for these tumors, multimodal therapies have meanwhile proven their efficacy. At present, pre- and postoperative chemotherapy and radiotherapy, targeted drug therapy, and stage-specific surgical approaches are all indispensable cornerstones of an individualized treatment for upper gastrointestinal malignancies. With such multimodal treatment, better outcomes comprising improved quality of life and prolonged survival have been achieved for patients. However, for many tumor entities and stages, the ideal combination and sequence of treatments is still being evaluated in clinical trials. Moreover, the value of novel approaches such as immunotherapy or robotic surgery remains a matter of research. In this Special Issue of Cancers, up-to-date original research, short communications, and comprehensive review articles on all modalities playing a role in the treatment of upper gastrointestinal malignancies have been published.